Exploring Student’s Computational Thinking in Number Line Patterns through the Dakon Context - Rahma Mutiari; Ali Shodikin (Universitas Negeri Surabaya, 2025)
This study explores how the traditional game Dakon supports students’ computational thinking in understanding number patterns. Computational thinking ability in this study includes four main indicators: decomposition, pattern recognition, abstraction, and algorithm. This study employed a case study design and a qualitative methodology and involved six students in grade VIII of junior high school who were purposively selected based on their level of mathematical ability. Data collection was conducted through observation of Dakon playing activities, number pattern-based written tests, semi-structured interviews as well as records. Data analysis was carried out, with triangulation of data from various sources to increase validity. The findings highlight strengths in decomposition and pattern recognition, while indicating the need for scaffolding in abstraction and algorithmic strategies. This finding confirms that the Dakon game not only strengthens mathematical understanding through a local cultural context, but is also able to build a deep and meaningful foundation of computational thinking. This research recommends the integration of traditional games as part of contextualized and fun math learning strategies to support acquiring skills for the twenty-first century.